2021
DOI: 10.1186/s12968-021-00797-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial extracellular volume by T1 mapping: a new marker of arrhythmia in mitral valve prolapse

Abstract: Objectives We aimed to evaluate the relationship between mitral annular disjunction (MAD) severity and myocardial interstitial fibrosis at the left ventricular (LV) base in patients with mitral valve prolapse (MVP), and to assess the association between severity of interstitial fibrosis and the occurrence of ventricular arrhythmic events. Background In MVP, MAD has been associated with myocardial replacement fibrosis and arrhythmia, but the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Tissue characterization is another piece of the MVP puzzle that CMR adds. In fact, the connection between MVP with or without MAD and macro-fibrosis is well established, as described by the group of the Padua University [11,14] and then confirm by others [15,[43][44][45], which involves the basal inferolateral wall (non-ischemic pattern as mid-wall striae or patchy are the most common) and papillary muscles, particularly those segments adjacent to the posteromedial papillary muscle even with only mild MR (Figure 7). Basso et al [11] also demonstrated that VA with RBBB morphology originated from the LV inferobasal wall near the mitral annulus, where myocardial fibrosis was either detected by CMR (LGE) in patients or by histology in SCD patients.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 58%
See 1 more Smart Citation
“…Tissue characterization is another piece of the MVP puzzle that CMR adds. In fact, the connection between MVP with or without MAD and macro-fibrosis is well established, as described by the group of the Padua University [11,14] and then confirm by others [15,[43][44][45], which involves the basal inferolateral wall (non-ischemic pattern as mid-wall striae or patchy are the most common) and papillary muscles, particularly those segments adjacent to the posteromedial papillary muscle even with only mild MR (Figure 7). Basso et al [11] also demonstrated that VA with RBBB morphology originated from the LV inferobasal wall near the mitral annulus, where myocardial fibrosis was either detected by CMR (LGE) in patients or by histology in SCD patients.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 58%
“…Bui at al [46] showed that patients with MVP had shorter postcontrast T1 times (higher fibrosis), particularly those with c-VA compared with patients without c-VA. In the retrospective study of Pavon et al [43], LGE was observed in 47% of patients with MVP and MAD, but 87% of the MVP and MAD patients had an extracellular volume (ECV) above the upper limit of normal (>27%). In addition, an ECV >27% was not only found in 93% of LGE-positive patients, but also in 81% of LGE-negative patients, and ECV was increased in all myocardium adjacent to the insertion of the prolapsing valve and not only in the inferobasal and inferolateral region.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…This fibrosis might be the arrhythmogenic substrate in MVP and is identifiable with LGE [ 62 ]. Besides LGE, focal and diffuse fibrosis in patients with MVP could also be identifiable with T1-mapping and myocardial extracellular volume quantification, as shown by Guglielmo et al [ 63 ] and Pavon et al [ 64 ]. Applying these two techniques reduces the use of contrast infusion in CMR.…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 77%
“…Mitral valve prolapse (MVP) is a valvular abnormality that has been associated with sudden cardiac death [ 62 ]. While echocardiography is well suited for diagnosing MVP, CMR can advance the identification of an arrhythmogenic substrate [ 62 , 63 , 64 ]. MVP is defined by superior displacement of one or both leaflets of the mitral valve into the left atrium [ 65 ].…”
Section: The Use Of Multiple Imaging Modalitiesmentioning
confidence: 99%
“…A recent histopathologic analysis of MVP with SCD also suggested that MVP patients may have a more diffuse type of fibrosis compared with controls [75]. This diffuse myocardial fibrosis can be identified with T1 mapping or with increased myocardial extracellular volume [72,77]. Taken together, a growing body of evidence suggests histologic fibrosis, both diffuse and focal to the papillary muscles and inferolateral wall, strongly correlate with arrhythmias and can be accurately assessed non-invasively with CMR utilizing post-contrast LGE sequences and other sequences focused on diffuse fibrosis.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%